Development of a Human Factors Principles-Based Design Tool for Engineers. (September 2014) - Sebok, Angelia; Quesada, Stacey; Andre, Terence
Designing for users involves many challenges, including understanding the situation in which the end users will be working. In a recent NASA Small Business Innovative Research effort, a research team developed a software tool to help engineers and human factors specialists share human factors information and project-specific data. The resulting product was a software tool called the Human Factors Analysis Support Tool (H-FAST). This paper describes a project to provide a proof of concept to extend H-FAST's capabilities. In this effort, we developed the Automated Guidance Assessment Tool (AGAT). AGAT assesses a control panel design in terms of its adherence to human factors principles, and provides relevant feedback to engineers in the form of targeted recommendations and access to relevant human factors standards.